2020
DOI: 10.1177/0003134820945204
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Versus Oral Acetaminophen in Outpatient Cystoscopy Procedures: Retrospective Comparison of Postoperative Opioid Requirements and Analgesia Scores

Abstract: Purpose To assess if the choice of acetaminophen formulation (intravenous vs oral) when administered preoperatively for ambulatory cystoscopy procedures is associated with differences in anesthetic outcomes. Methods Medical records of adult patients undergoing ambulatory cystoscopy procedures at an outpatient procedural center from July 1, 2014, through November 30, 2017, were abstracted. The association between anesthetic outcomes (severe pain, rescue opioids, postoperative nausea, and vomiting) and acetamino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Moreover, other drugs can also be used successfully, such as pipemidic acid, phenazopyridine and paracetamol [ 61 , 68 ]. A comparison between the oral administration of pipemidic acid, phenazopyridine and diclofenac indicated that pipemidic acid was superior to the other two drugs (based on the VAS score) [ 61 ].…”
Section: Pharmacotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, other drugs can also be used successfully, such as pipemidic acid, phenazopyridine and paracetamol [ 61 , 68 ]. A comparison between the oral administration of pipemidic acid, phenazopyridine and diclofenac indicated that pipemidic acid was superior to the other two drugs (based on the VAS score) [ 61 ].…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Finally, a study comparing oral and intravenous paracetamol use in ambulatory CS showed no difference in pain levels, with more complications after intravenous administration of acetaminophen [ 68 ]. This leads to the conclusion that parenteral administration of analgesics should be avoided unless necessary.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Las técnicas analgésicas se han modificado para llevar este manejo al ámbito domiciliario del paciente y, en este grupo seleccionado de pacientes, la posibilidad de realizar analgesia invasiva domiciliaria como gran avance en el control del dolor es contundente. El uso de técnicas regionales continuas podría simplificar el tratamiento y ahorrar costos de enfermería [5], [6], [7].…”
unclassified
“…We recognize that since our initial inquiry and literature search in early 2017, there are multiple published studies at the time of publication of our study (2020). [5][6][7][8][9][10][11][12][13][14][15] Because at the time of protocol development there was no published effect size of the primary outcome variable, the authors calculated a sample size required to detect a clinically significant difference in pain scores. The consensus of the study team was that a 2point difference on a 0 to 10 pain rating scale would be clinically significant.…”
mentioning
confidence: 99%